Educating teachers of the visually impaired in the context of educational and social changes – a research report - Czerwińska, Kornelia; Miler-Zdanowska, Kamila (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Changes in the ways of performing professional roles of special education teachers entail the need to develop new solutions for academic education for teachers of the visually impaired. The assessment of the content and forms of the previously proposed education for teachers of the visually impaired from the perspective of the usefulness of their professional competencies may be helpful in the determination of the needed directions of changes in this respect. The aim of the article is to describe and analyse the results of comparative research on visual impairment pedagogy graduates educated in the system of 5-year uniform master’s studies and 3-year bachelor’s studies, concerning the course of their educational and professional paths.